Collaborative Leadership in Crisis Management: A Case Study of Cross-Sectoral Policy Integration in Disaster Management in Indonesia - Mulyaningsih Mulyaningsih; Haziq Idris; Rina Farah (Journal of Social Science Utilizing Technology, 2026)
Background. Indonesia faces increasingly complex disaster management challenges due to the high frequency of natural disasters and the involvement of multiple institutional sectors in crisis response processes. Fragmented governance structures, overlapping institutional responsibilities, and limited interagency coordination often hinder effective disaster management implementation. Collaborative leadership has therefore emerged as an important governance approach for strengthening cross-sectoral policy integration and improving institutional responsiveness during crisis situations. Purpose. This study aimed to examine the role of collaborative leadership in supporting cross-sectoral policy integration within disaster management systems in Indonesia. Method. Qualitative case study methodology was employed through in-depth interviews, field observations, and document analysis involving governmental agencies, humanitarian organizations, community leaders, and disaster management stakeholders across selected disaster-prone regions. Results. The findings revealed that collaborative leadership significantly improved communication quality, institutional trust, resource coordination, and policy coherence among participating stakeholders. Participatory decision-making, adaptive coordination mechanisms, and transparent communication systems were identified as critical factors supporting effective crisis governance and integrated disaster management implementation. Collaborative leadership additionally strengthened community participation and institutional flexibility during emergency response and recovery processes. Conclusion. This study concludes that collaborative leadership constitutes a strategic governance capacity for enhancing disaster resilience and strengthening integrated crisis management systems in Indonesia. Effective disaster governance therefore requires inclusive coordination structures, adaptive policy integration mechanisms, and sustained interorganizational collaboration across multiple governance sectors.